PENERAPAN SISTEM INFORMASI ONLINE SMK PUTRA ANDA BINJAI BERBASIS WEBBASE - Sinurat, Sylvia Natalia; Syahputri, Heni; Novriyenni, Novriyenni; Maulita, Yani (STMIK Kaputama, 2018)
Currently the increasingly rapid development of internet technology and is one example of effective information technology utntuk dissemination of information because the internet is a means of communication that are global. Make it easy for students and teachers can access all the information anytime and anywhere. With the rapid technological developments, education facilities and infrastructure must also follow each person can easily see the information necessary school perform various types of information. The problem that occurs is in terms of providing information that is still done manually done on your son SMK Binjai by way of prospective students must come to school to register. With this situation it is not effective and efficient. Utilizing a computerized system is much needed considering the development of rapid technological knowledge so that all activities can be done quickly and accurately without disturbing other activities. One way to overcome the above is to create a web-based information system by using a database that consists of a few tables so that registration can be done online in a way. It also can help the school, especially the new admissions committee to log the students become more easily, effectively and efficiently.